Ranking Systemically Important Financial Institutions - Mardi Dungey; Matteo Luciani; David Veredas (Tinbergen Institute, 2012)
We propose a simple network–based methodology for ranking systemically important financial institutions. We view the risks of firms –including both the financial sector and the real economy– as a network with nodes representing the volatility shocks. The metric for the connections of the nodes is the correlation between these shocks. Daily dynamic centrality measures allow us to rank firms in terms of risk connectedness and firm characteristics. We present a general systemic risk index for the financial sector. Results from applying this approach to all firms in the S&P500 for 2003–2011 are twofold. First, Bank of America, JP Morgan and Wells Fargo are consistently in the top 10 throughout the sample. Citigroup and Lehman Brothers also were consistently in the top 10 up to late 2008. At the end of the sample, insurance firms emerge as systemic. Second, the systemic risk in the financial sector built–up from early 2005, peaked in September 2008, and greatly reduced after the introduction of TARP and the rescue of AIG. Anxiety about European debt markets saw the systemic risk begin to rise again from April 2010. We further decompose these results to find that the systemic risk of insurance and deposit–taking institutions differs importantly, the latter experienced a decline from late 2007, inline with the burst of the housing price bubble, while the former continued to climb up to the rescue of AIG.
Keywords: G01; G10; G18; G20; G28; G32; G38; 330; Systemic risk; ranking; financial institutions; Lehman; Finanzsektor; Multinationales Unternehmen; Systemrisiko; Ranking-Verfahren; Welt